Prevalence of Gastrointestinal Parasites in Slum Children of Dhaka City: Comparison of Two Coprological Methods - Hosna, Asmaul; Khanum, Hamida (Bangladesh Journal of Zoology, 2023)
The present study aimed to measure the prevalence of intestinal parasites among children with gastrointestinal tract infections from different slum areas of Dhaka. Furthermore, a comparison was made of the accuracy of direct smear (DS) and formol-ether concentration (FEC) techniques in the detection of infection. The overall prevalence of parasitic infection was 72.46% with a combined method. By direct smear, 2 species of protozoa (11.59%), 2 species of cestode (5.07%) and 4 species of nematode (18.12%) parasites were detected whereas by formol – ether concentration method, 5 species of protozoa (28.26%), 1 species of Trematode (1.44%), 2 species of cestode (17.39%) and 5 species of nematode (79.71%) parasites were detected. By direct smear (DS) and formol-ether concentration (FEC) the prevalence of intestinal parasites was 42% and 58% respectively. Ascaris lumbricoides was the most common parasite detected by both formol-ether concentration (37.68%) and direct smear method (7.97%). A statistically significant association (P < 0.001) was found between the test methods, age groups and months with parasitic infection. Direct smear showed less sensitivity than formol-ether concentration technique (100%). The diagnostic performance of formol-ether technique for the diagnosis of intestinal parasites in slum children was remarkably higher as related to direct smear in the present study. Therefore, the DS and FEC combined techniques should be used as routine investigative techniques for the identification of intestinal parasites. Henceforth, it is advantageous to use the formol-ether method to complement the direct smear method. Bangladesh J. Zool. 50(3): 353-361, 2022